Diferenciación entre variedades de cacao con base a su susceptibilidad a la infección con Ceratostomella fimbriata (E. and H.) Elliot, en el Ecuador - Desrosiers, Russell (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Indications of a strong relationship between susceptibility to Ceratostomella disease of cacao and the Criollo variety of cacao is suggested from observations of the relative susceptibility of Criollo, Forastero and Trinitario cacao at the Tropical Experiment Station in Ecuador. In an area planted to a collection of cacao varieties, 54 percentage of the plants displaying a predominance of Criollo characteristics were infected or had died of the disease whereas only 2.5 percentage of other types were infected and none dead. It is suggested that large plantings of Criollo cacao are likely to suffer severely from this disease whereas, in plantings of Trinitario cacao, which combines germ plasm of Criollo and Forastero, only those segregates having a predominance of Criollo germ plasm are likely to be susceptible.